Is the quality of skin cancer screening in Germany related to the specialization of the physician who performs it?: Results of a nationwide survey among participants of skin cancer screening - Görig, Tatiana; Schneider, Sven; Breitbart, Eckhard W.; Diehl, Katharina (Photodermatology, photoimmunology & photomedicine, 2021)
Background Skin cancer screening (SCS) is an important measure for secondary prevention of skin cancer, which is the most common cancer type worldwide. This study aimed to describe patient-reported quality of SCS in Germany according to the specialization of the performing physician and different patient characteristics. Methods Data from 1260 participants 35-65 years of age (54.4% female) who underwent SCS and participated in National Cancer Aid Monitoring in 2019 were evaluated using chi-squared tests. Results Waiting times for SCS from a dermatologist were significantly longer than those for other physicians (31.1 versus [vs.] 15.7 days; P < .001). Each body area examined during the standardized inspection was examined significantly more frequently by dermatologists than by other physicians (eg, upper body, 96.6% vs. 91.7%; P < .001). Dermatologists more often offered consultation for skin cancer prevention (74.0% vs. 67.6%; P = .026) and provided written information (47.8% vs. 34.8%; P < .001). Patients with statutory insurance had to pay more frequently for additional services during SCS from a dermatologist than from other physicians (24.7% vs. 17.1%, P = .012). Conclusion Results of this study revealed differences in the provision of preventive information and the quality of visual examination during SCS between dermatologists and other physicians. These results highlight the need for quality assurance measures.
Gesehen am 30.10.2023